A Study of Students from Academic Programs in British Columbia's Community Colleges - Dennison, John D.; Forrester, Glen; Jones, Gordon (Canadian Journal of Higher Education, 1982)
One of the major features of British Columbia's community colleges has been the university transfer programs which provide the opportunity for students to earn credits towards a university degree. Previous studies have shown, however, that only a small percentage of students from these programs actually transfer to a university. This study was designed to examine the behaviour of those students who complete academic or university transfer courses in a college, but do not continue their study in a university. Data were gathered from approximately 4,000 students from 14 colleges in the 1979-80 calendar year. The results of the study indicate that students pursue academic credit courses primarily for per- sonal development rather than for university transfer. The community colleges provide an intellectual and cultural environment, particularly for mature students who for geographic, educational or socio-economic reasons would not have been able to continue their education beyond secondary school The study provided an important insight into the changing role of the community college. Originally designed as an institution for college age students to begin university level study, it has become a multi-purpose educational resource for a wide segment of society.